Immediate and short-term outcomes of percutaneous coronary intervention in patients with stable and multivessel coronary artery disease, intolerant to coronary artery bypass grafting - Sh. Sh. Zaynobidinov; D. A. Khelimskii; A. A. Baranov; A. G. Badoyan; A. Yu. Tsydenova; R. A. Naydenov; O. V. Krestyaninov (Российский кардиологический журнал)
Aim. To evaluate immediate angiographic and clinical outcomes of percutaneous coronary intervention (PCI) in patients with stable and multivessel coronary artery disease (CAD), intolerant to coronary artery bypass grafting.Material and methods. This retrospective study included 307 patients with multivessel CAD who underwent myocardial revascularization using PCI between 2013 and 2022. Mortality, complications, and clinical parameters after the procedure were assessed in the early postoperative period.Results. Revascularization was successful in 94,9% of patients, The mean surgery duration was 59,0±28,9 min. The incidence of major adverse cardiac and cerebrovascular events was 3,1%. Complete revascularization was achieved in 54 (17,6%) patients. There were following independent predictors of incomplete myocardial revascularization according to multivariate regression analysis: high EuroSCORE II (odds ratio (OR) 0,83, 95% confidence interval (CI): 0,68-1,0; p=0,047), SYNTAX (OR 0,93, 95% CI: 0,89-0,97; p=0,001), and J-CTO (OR 0,68, 95% CI: 0,49-0,94; p=0,0018) scores.Conclusion. PCI in patients with multivessel CAD and intolerance to coronary artery bypass grafting is a safe procedure with low inhospital mortality and postoperative complications. PCI in this cohort of patients is associated with a high rate of procedural success. Additional studies, including randomized trials, are needed to assess the long-term prognosis in this cohort of patients.